Functional study of CYP90A1 and ALDH3F1 gene obtained by transcriptome sequencing analysis of Brassica napus seedlings treated with brassinolide - Gan, Qingqin; Luan, Mingbao; Hu, Maolong; Liu, Zhongsong; Zhang, Zhenqian (Frontiers in Plant Science, 2022)
Sclerotinia disease and weeds of Brassica napus greatly reduce crop yields. However, brassinolides can improve the resistance of plants to sclerotinia diseases and herbicides. In this study, we investigated the effects of brassinolide on the occurrence, physiological indices, yield, and gene expression of Fanming No. 1 seeds under sclerotinia and glufosinate stress. The results showed that soaking of the seeds in 0.015% brassinolide for 6 h reduced the incidence of sclerotinia by 10%. Additionally, in response to glufosinate stress at the seedling stage, the enzyme activities of catalase and superoxide dismutase increased by 9.6 and 19.0 U/gFW/min, respectively, and the soluble sugar content increased by 9.4 mg/g, increasing the stress resistance of plants and yield by 2.4%. LHCB1, fabF, psbW, CYP90A1, ALDH3F1, ACOX1, petF, and ACSL were screened by transcriptome analysis. ALDH3F1 and CYP90A1 were identified as key genes. Following glufosinate treatment, transgenic plants overexpressing ALDH3F1 and CYP90A1 were found to be resistant to glufosinate, and the expression levels of the ALDH3F1 and CYP90A1 were 1.03–2.37-fold as high as those in the control. The expression level of ATG3, which is an antibacterial gene related to sclerotinia disease, in transgenic plants was 2.40–2.37-fold as high as that in the control. Our results indicate that these two key genes promote plant resistance to sclerotinia and glufosinate. Our study provides a foundation for further studies on the molecular mechanisms of rapeseed resistance breeding and selection of new resistant varieties.